The Role of Balunijuk Indigenous Communities Against Unconventional Mining a Malay Inner Perspective - Ndaru Satrio; Muhammad Syaiful Anwar (Kosmik Hukum, 2023)
This research was conducted in Balunijuk Village, whose indigenous people prefer to reject tin mining as their way of life. It is interesting for the author to examine the role of the indigenous people of Balunijuk village in fighting unconventional mines from an inner Malay perspective and how the methods used by the indigenous people of Balunijuk village to fight unconventional mines from an inner Malay perspective. The research method used is socio-legal. The role of the indigenous people of Balunijuk Village in fighting Unconventional Mining within the Malay inner framework includes (1) protecting the living space of indigenous peoples, (2) preventing corrupt acts in the living areas of indigenous peoples, (3) preventing the criminalization of indigenous peoples. The method used by the Balunijuk indigenous people against the existence of unconventional mining is to use existing local wisdom, namely ampak. The advice given is that the existence of local wisdom that has sacred values should get a better place in solving problems that arise. Keywords: Role, Indigenous Peoples of Balunijuk Village, Unconventional Mining